A Study of the thermodynamic parameters (functions) of complexes formation of Sulfanilamid with metal ions and DL-Alanine by potentiometric method - Luma Abaas Gaasm (Tikrit Journal of Pure Science)
The current study deals with the preparation of disulfonalmide complexes composed of the sulfanilamid  drug , the salt of chromium(III) and the trisulfonalmide complexes composed of the  sulfonalmide drug , the metal salt and the amino acid (alanin), as well as study in the stability constant of each complex and making a comparison between them . The obtained results show that the tricomplex stability constant is higher than the dicomplex stability constant due to the existence of the amino acid in the tricomplex which makes greater stereo structure and eventually easier interaction. Besides the thermodynamic functions in this experiment have been studed  since they cause a chemical spontaneous reaction and a random arrangement in system.